Empowerment of Coastal Communities Through Community-Based Ecotourism in Telukawur Village, Annual District, Jepara Regency - Ahmad Nursahid; Aris Sunarya; Sri Roekminiati; Ika Devy Pramudiana (International Journal of Social Science and Humanity, 2025)
This study aims to describe the process of empowering coastal communities through the development of community-based ecotourism in Telukawur Village, Tahunan District, Jepara Regency. This study uses a descriptive qualitative approach with a case study method. Data was collected through interviews, observations, and documentation. The results of the study show that empowerment is carried out through skills training, strengthening local institutions, developing cultural and environment-based tourist attractions, and providing basic tourism facilities that are managed directly by the community. Ecotourism management is carried out in a participatory and mutual manner, reflecting the independence and ownership of the community over tourist destinations. This approach not only improves economic well-being, but also strengthens the preservation of the environment and local cultural values. This research emphasizes the importance of synergy between the community, government, and external parties in creating community-based sustainable tourism.